Characterization of bonding property in asphalt pavement interlayer: A review - Kai Yang; Rui Li (Journal of Traffic and Transportation Engineering (English ed. Online), 2021)
Higher requirements are put forward for interlayer bonding property with the increase of traffic load, including bearing capacity and durability. Typical diseases caused by insufficient adhesion between layers are slippage cracking, de-bonding and pavement deformation. The correct characterization of bonding property becomes necessary with evolving concerns of interlayer failure and material innovations. In the past forty years, many researches have focused on the evaluation of interlayer bonding property, and some valuable conclusions have been drawn. In this review, the mechanism, evaluation method and influencing factors of the interlayer bond strength are reviewed. The common test equipment can be classified into the shear, pull-off and torsion test. Different influence factors are analyzed including tack coat property, temperature, asphalt aging and surface condition. It is recommended to select the appropriate tack coat rate, and apply the tack coat under the conditions of clean, dry, high surface texture and good compaction. However, the interlayer failure mechanism and the interaction between the different influencing factors need to be further studied. The future work can focus on the correlation between different test methods and evaluation parameters, which would address the lack of harmonization or consistency among various evaluation approaches. Meanwhile, it is significant to add the evaluation of interlayer bonding property into the system of pavement design.